The Texas Chainsaw Massacre - Marcus Nispel; Biel, Jessica, 1982-; Jonathan Tucker; Erica Leerhsen; Mike Vogel; Eric Balfour; Andrew Bryniarski; R Lee Ermey (USA New Line Cinema, 2003)
A group of college kids, on their way back from scoring drugs in Mexico, run into a hitchhiker who has just survived a horrific massacre from the night before. They try to help the girl, but in the process end up falling prey to her mysterious fear. It happens to be wielding a chainsaw...
A group of friends passing through are stalked and hunted down by a deformed killer with a chainsaw in order to sustain his poor family who can only afford to eat what they kill.
Kim Henkel
Language : English
Subtitle : English
Keywords: Crime; Horror; Thriller